Retrospective study of oral and maxillofacial lesions in older Taiwanese patients. (21st February 2014) - Lei, Frank; Chen, Jing‐Yi; Wang, Wen‐Chen; Lin, Li‐Min; Huang, Hsien‐Cheng; Ho, Kun‐Yen; Chen, Yuk‐Kwan
Abstract : Objective: The aim was to provide information regarding oral and maxillofacial (OMF) lesions in an older Taiwanese population. Background: The rate of increase of older people in Taiwan is expected to be rapid. OMF lesions are very frequent in the older population, but no studies have been performed on these lesions in Taiwan. Materials and methods: OMF cases (between 2000 and 2011) in geriatric patients (≥60 years of age) with records of age, sex and histological diagnoses were retrieved from the Oral Pathology Department of our institution. These lesions were classified into four main categories: tumour/tumour‐like reactive lesions, cystic/pseudocystic lesions, inflammatory/infective lesions and other miscellaneous lesions. Results: Six thousand seven hundred and twenty‐six lesions were collected from a total of 39 503 OMF lesions in older Taiwanese patients in this study. Most of these lesions were distributed in the inflammatory/infective group, followed by tumour/tumour‐like reactive lesions. Squamous cell carcinoma was the most common lesion, and, additionally, there was a high frequency of oral potentially malignant disorders. Conclusions: The present study showed trends similar to previous reports from other countries. However, some detailed information was different, perhaps due to the different criteria and different geographic distribution. Worthy of note, our results indicated that screening for oral potentially malignant disorder and oral malignancy in the older population is essential.